Comparison of the Use of Desflurane vs. Propofol in Aortic Valve Replacement Surgery: Differences in Nephroprotection: An Explorative and Hypothesis-Generating Study - Guerrero Orriach, Jose Luis; Malo-Manso, Alfredo; Nuñez Galo, Mercedes; Bellido Estevez, Inmaculada; Ruiz Salas, Amalio; Cruz Mañas, Jose; Garrido-Sanchez, Lourdes; Gonzalez-Alvarez, Laura (Life (Basel, Switzerland), 2022)
Introduction: The cardioprotective effect of halogenated drugs in cardiac surgery has been the subject of several studies. However, there is scarcity of data on their potential nephroprotective effects. Aortic valve replacement and coronary revascularization are the most frequent cardiac surgery procedures. The objective of this explorative study was to examine the effect of desflurane vs. propofol on renal function, when administered in aortic valve replacement surgery, including the extracorporeal circulation period. Method: A quasi-experimental prospective study was performed in 60 patients, who were allocated to receive either desflurane or propofol intraoperatively during aortic valve replacement surgery. As a hypnotic, group 1 received propofol, whereas group 2 received desflurane. Markers of renal function and level of cardiac preservation were determined based on biochemical parameters (troponin I, NTProBNP). Results: In the propofol group, there were significant variations between postoperative values of urinary NGAL and creatinine and baseline values. In contrast, no variations were found in the desflurane group in terms of hemodynamic parameters and myocardial damage. Conclusions: The use of propofol vs. desflurane during aortic valve replacement surgery is associated with a decrease in renal function.